Perlindungan Hukum Rahasia Dagang Terhadap Masyarakat Ekonomi Asean (MEA) - Indriyana Dwi Mustikarini (Faculty of Law Hang Tuah University, 2016)
Countries as member of the ASEAN established economic community to provide easy entry and exit of goods from the Southeast Asia countries. It aims to creating fail economic growth in Southeast Asia, improving living standards and reducing the poverty. This situation had an impact on the existence of intellectual property rights, primarily trade secrets to be protected because the trade secrets do not legally require registration. The research method uses a legal research. The legal research is a process of finding the laws, legal principles and the legal doctrines in order to answer the legal issues. The approach that is used in the legal research is statute approach. The results of the research are that legal protection of trade secrets toward the ASEAN economic community covers producing methods, processing methods, selling methods, or other information on technology and/or business that has added values but the public do not know. Property rights can be obtained without registration. The legal protection of trade secrets is regulated in TRIPS and Act No. 30 of 2000. However, regulation of property rights on the trade secret rights is still not available, so there is legal uncertainty.